Sex determination of the Bosnian-Herzegovinian population based on odontometric characteristics of permanent lower canines (Journal of Health Sciences, 2013)
Introduction: Sex determination is one of fi rst and most important steps in identifying disintegrated bodies and skeletal remains. During the exhumation of bodies from the mass graves and archaeologicalexcavations, it is quite often the case that not all bones of one person are found, therefore, teeth and the scull are the only true identifi cation material. Canines are teeth most appropriate for sex determination.The aim of the research was to determine sex identity of the Bosnian-Herzegovinian population based on odontometric characteristics of permanent lower canines.Methods: The research sample included 180 patients of the Dental Offi ce, of both sexes. All patients with permanent lower right and left canines, without caries, with healthy state of gingiva and periodontium,without crown restorations were included in the research. Measurement was done directly in the patients' mouth using a digital sliding caliper. Greatest mesiodistal width of the lower right and left canine and intercuspal distance of the lower jaw were measured.Results: All parameters were higher in case of male, including Mandibular Canine Index (MCI) (p<0.01). The precision of appraising the sex identity for the Bosnian-Herzegovinian population, based on MCI on the right, amounts 68.89% and 68.54% on the left.Conclusions: The study showed that right canines are signifi cantly broader than the left ones and they are broader in case of males. Lower right canines, that is, MCI on the right, indicates greater accuracy insex determination in relation to left lower canines. The accuracy in sex determination for all variables is higher for the female.